PENGARUH PENGALAMAN, KOMITMEN PROFESIONAL, KOMITMEN ORGANISASIONAL, IDEALISME, DAN RELATIVISME PADA ETIKA AUDITOR - Mustika, Tri Krisna Yoga; Jati, I Ketut (E-Jurnal Akuntansi; Vol 18 No 3 (2017), 2017)
The purpose of this study was to determine the effect of experience, professional commitment, organizational commitment, idealism and relativism in ethics auditor Public Accounting Firm in Bali. The study was conducted in 2016. The data was collected using a questionnaire. The number of samples in this study were 58 auditors and are selected based on purposive sampling method, which has audit experience at least 1 year. In this study, H1 test results show that the experience affects the ethics auditor KAP in Bali. H2 results indicate that the effect on the professional commitment to ethical auditor KAP in Bali. H3 results indicate that organizational commitment to ethics berpenagruh auditor KAP in Bali. H4 results show that the effect on the ethical idealism auditor KAP in Bali. The results show that the H5 effect on ethical relativism auditor KAP in Bali.
Keywords: Ethics, Experience, Professional Commitment, Organizational Commitment, Idealism, Relativism